2013
DOI: 10.1108/17542731311286405
|View full text |Cite
|
Sign up to set email alerts
|

Quality standards: integration within a bereavement environment

Abstract: Purpose -The purpose of this paper is to examine the means by which one UK local authority obtained certification of its Bereavement Service against ISO9001, ISO14001, and ISO27001. It aims to explain the processes that were followed, highlight the problems that were encountered, and show how these were overcome. Design/methodology/approach -The paper adopts a case study approach. The case study emerged from a broader grounded theory study which is outside the scope of this paper. Findings -This paper demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
18
0
3
Order By: Relevance
“…And, though not always the company integrated the two systems, it was observed that there was a learning process in their routines (Brendler & Brandli, 2011). Crowder (2013) analyzed the factors that determined a successful integration between the environmental and quality systems, which are the support to senior management, coordination within the organization, leadership, smartness and appropriate approach.…”
Section: Relations Between Iso 14001 With Iso 9001mentioning
confidence: 99%
“…And, though not always the company integrated the two systems, it was observed that there was a learning process in their routines (Brendler & Brandli, 2011). Crowder (2013) analyzed the factors that determined a successful integration between the environmental and quality systems, which are the support to senior management, coordination within the organization, leadership, smartness and appropriate approach.…”
Section: Relations Between Iso 14001 With Iso 9001mentioning
confidence: 99%
“…This leads to subsystems valorisation enhancing common aspects synergies within different standards (Crowder, 2013;Renzi & Cappelli, 2000) and improving organisational efficiency and profitability (Abrahamsson, Hansson, & Isaksson, 2010). This type of management promotes an effective management model that can be integrated with other management requirements from the point of view of organisations' top management (Waclawovsky & Batiz, 2010), and also a sustainability warranty (Kuei & Lu, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Ambos sistemas tienen efectos positivos en la satisfacción de clientes, la reducción del coste, la diferenciación y la mejora de la imagen y la eficiencia organizacional (Abad, Dalmau, & Vilajosana, 2014;Bernardo, Simon, Tarí, & Molina-Azorín, 2015;Crowder, 2013;de Oliveira, 2013;Ferreira Rebelo, Santos, & Silva, 2014;Karapetrovic & Casadesús, 2009;Santos, Mendes, & Barbosa, 2011;Simon & Douglas, 2013;Simon, Karapetrovic, & Casadesus, 2012;Simon, Karapetrovic, & Casadesús, 2012;Wagner, 2007). Además, la integración en sí misma también reduce costes y mejora la comunicación y la gestión (Beckmerhagen, Berg, Karapetrovic, & Willborn, 2003;Molina-Azorín et al, 2009;Rodríguez & Ricart, 2000;Wilkinson & Dale, 1999;Zeng, Tian, & Shi, 2005;Zutshi & Sohal, 2005).…”
Section: Gestión De Calidad Y Medio Ambienteunclassified